EFFECTS OF LONG-TERM FERTILIZATION ON YIELD OF SIDERATES AND ORGANIC MATTER CONTENT OF SOIL IN THE PROCESS OF RECULTIVATION - D. Terzi; V. M. Popovi; N. Mali; J. Ikanovi; V. Rajii; S. Popovi; M. Lon arand V. Lon arevi (Journal of Animal and Plant Sciences, 2019)
The aim of this research was to determine the possibility of increasing organic matter content in humusless deposol topsoil and forming of a more favourable adsorptive complex by introducing green manure. Green manure biomass came from these compound plant species: winter rye + common vetch, forage pea + rapeseed mustard and Sudan grass. Compound feed was sown on degraded soil (type deposol) of the Stanari coal mine. Applied cultivation practices included primary and secondary tillage and additional plant nutrition. Mineral fertilizers were applied: NPK 7:20:30 (400 kg ha-1) and CAN 27% (200 kg ha-1). One of the treatments included addition of bentonite clay as absorbent of nutrients. During intensive vegetation the growth of the green biomass was measured, the crops were harvested, cut and ploughed in deposol topsoil. Organic matter content in deposol was determined when soil samples were taken 6 months after green manure incorporation. The results show that the mineral fertilization of siderates significantly increased green biomass yield and Sudan grass gave two cuts, which positively affected the increase of organic matter content in soil.
Keywords: mixtures; degraded soil; mineral fertilizers; biomass yield; organic matter content